Determinants of the Accuracy of Islamic Banking Financial Reporting in Indonesia (Empirical Study on Indonesian Islamic Banking Listed on the IDX in 2018-2020) - Muhammad Apriansyah Putra; Yusmaniarti Yusmaniarti; Hesti Setiorini (Journal of Islamic Economics and Social Science (JIESS), 2022)
Timeliness of financial reporting can affect the value of benefits for users of financial statements. The delay in financial reporting is a bad image in the seen of investors and other external parties. This study aimed to determine the effect of profitability, liquidity, leverage, and firm size on the timeliness of financial reporting. The sample of this study was taken by using the total sampling method. The sample is the financial statements of Islamic banks from the last 3 years consisting of 15 Islamic banking companies with 45 research data (3 years x 15 sample companies). The data collection techniques used documentation and literature studies taken from the official website of the Indonesia Stock Exchange, namely www.idx.co.id as secondary data The technique of analyzing the data used descriptive statistical tests and hypothesis testing. The results of this study indicate that Profitability, Liquidity, and Leverage have no effect on the timeliness of the company's financial reporting. This can be seen from the P values Profitability: 0.900, Liquidity 0.338, Leverage 0.192 which greater than the significance level of 0.05, and the size of the company has an effect on the timeliness of the company's financial reporting. This can be seen from the P values which is smaller than the limit of significance value of 0.000 0.05 Hence, simultaneously profitability, liquidity, leverage, and firm size affect the timeliness of financial reporting.